Wet Impregnation Synthesis of Green NCC/TiO2 Hybrid Materials Derived from Oil Palm Empty Fruit Bunches - Teodora Merry Meriba Vica Juliana Br Lumbanraja; Raihan Navil Junizal; SINTA SORAYA SANTI; Ika Nawang Puspitawati; Perwitasari; Srie Mulnani; Sani; Adityas Agung Ramandani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The high volume of agricultural waste in Indonesia, particularly Oil Palm Empty Fruit Bunches (OPEFB), presents a significant opportunity for the development of sustainable, high-value materials. While Titanium Dioxide (TiO?) is widely recognized for its photocatalytic efficiency, its practical application is often hindered by particle agglomeration, which reduces its effective surface area. This research aims to overcome these limitations by synthesizing and characterizing a green hybrid material using Nanocrystalline Cellulose (NCC) derived from OPEFB as a renewable support matrix. The methodology involved the isolation of NCC through sequential delignification and acid hydrolysis, followed by the synthesis of the NCC/TiO? nanocomposite via the wet impregnation method. The research utilized Response Surface Methodology (RSM) to optimize the synthesis process. The process variables investigated included the NCC-to-TiO? ratio (10%, 20%, 30%, 40%, and 50% w/w) and stirring time (20, 40, 60, 80, and 100 minutes), with the final nanocomposite mass serving as the primary response. The results showed that the NCC yield from OPEFB was 43.78%. The optimum condition was achieved at an NCC ratio of 50% and a stirring time of 100 minutes, yielding a nanocomposite mass of 8.8975 grams. Characterization results that the high surface area of the NCC successfully stabilized the TiO? particles with particles measuring 27.52 nm. This study demonstrates that the integration of RSM with green material synthesis provides a highly effective and sustainable approach to valorising palm oil waste into functional photocatalytic hybrid materials. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land